Overview of the genesis of the legal regulation of administrative procedure in Poland - Markova, O. O.; Маркова, О. О. (Одеса : Гельветика, 2021)
У цій статті автор досліджує історико-правовий аспект виникнення адміністративної процедури в Польщі. Були проаналізовані історико-правові події, що вплинули на становлення адміністративної процедури в Польщі. Польща була країною-правонаступником австрійського досвіду у сфері адміністративної процедури як у питанні правового регулювання адміністративної процедури, так і в характері моделі адміністративної процедури. Доказом цього була законотворча діяльність польського законодавця, Президента і діяльність Вищого адміністративного суду Польщі. Перша повна польська кодифікація адміністративно-процесуального права відбулася 22 березня 1928 року у вигляді Указів, виданих Президентом Республіки Польща, які мали силу закону: про адміністративне провадження, про примусове провадження в адміністрації, а також про кримінально-виконавче провадження, про виконавче провадження в адміністрації, які діяли до моменту прийняття Кодексу про адміністративне провадження в 1960 році. За основу законодавець взяв австрійський Закон про адміністративну процедуру від 21 липня 1925 р. Судова практика Вищого Адміністративного суду Польщі також мала значний вплив на розробку і тлумачення положень про адміністративне провадження. З огляду на поетапний розвиток кодексу в напрямі розширення кількості проваджень, які він регулював, ми можемо стверджувати, що польський законодавець прагнув об’єднати найбільш важливі провадження в одному акті з метою вироблення уніфікованого підходу до адміністративної процедури.

In this article the author conducted a study related to the consideration of historical and legal issue of the emergence of administrative procedure in Poland. The historical and legal events which influenced the formation of administrative procedure in Poland have been analyzed. Poland was a successor country to the Austrian experience in the field of administrative procedure both in the question of legal regulation of administrative procedure and in the nature of the model of administrative procedure. A proof of that is the legislative activity of the Polish legislator, the President and the activity of the Supreme Administrative Court of Poland. The first full Polish codification of administrative procedural law took place on 22 March 1928 in the form of Decrees issued by the President of the Republic of Poland having the force of law: on administrative proceedings, on compulsory proceedings in administration, and on criminal and administrative proceedings, and on executive proceedings in administration, which were in effect until the adoption of the Code of Administrative Procedure in 1960. The legislator took as a basis the Austrian Administrative Procedure Act of 21 July 1925. The jurisprudence of the Supreme Administrative Court of Poland has also had a significant impact on the development and interpretation of provisions on administrative proceedings. Considering the gradual development of the Code towards increasing the number of proceedings regulated by it, we can affirm that the Polish legislator aimed at combining the most important proceedings in a single act in order to create a unified approach. The new Code created a procedure that allowed for a harmonious relationship between the administration and the citizen, while at the same time providing for the possibility for citizens to defend their rights in cases of abuse of power by the authorities.
Markova O. O. Overview of the genesis of the legal regulation of administrative procedure in Poland / O. O. Markova // Актуальні проблеми держави і права : зб. наук. пр. Вип. 91 / редкол.: Г. I. Чанишева (голов. ред.) та ін. – Одеса : Гельветика, 2021. – С. 123-127.
Keywords: адміністративна процедура; історико-правові події; генезис правового регулювання; Research Subject Categories::LAW/JURISPRUDENCE; administrative procedure; historical and legal events; genesis of legal regulation